Implementasi Hardware Redundancy Pada Sistem Akuisisi Data Sensor Dengan Menggunakan Metode Hot Standby Sparing - Arie Prayogo Pangestu; Sabriansyah Rizqika Akbar; Primantara Hari Trisnawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Currently there are many products to monitor an object from various vendor service system providers that are used. The intended product is a group of sensors with interconnected microcontrollers to provide information of what the sensors capture an object condition, one of which is used for monitoring water conditions. When the water in the ponds is turbid, dirty, the water temperature increased and the salt content is irregular it will affect the quality of the fishpond. Sometimes some sensors on the monitoring system can be damaged, due to factors from within and from outside. Therefore, a system that is able to redundancy the main system in case of error. In this study there are three sensors namely temperature sensor, turbidity and salinity sensors in each master module and slave and using Hot Standdby Sparing method. This method is a way of completion so that the module that will be used as slave module remain alive or in idle condition even though it goes into sleep condition and ready to replace master module when there is system error. From the test results, the master module and slave module can work properly. The slave module can redundate the master module when there is an error on the sensor as well as the power failure of the master module, and the system can avoid race conditions between master and slave modules when first turned on.